Mengukur Peran Mediasi E-Satisfaction dalam hubungan antara E-Trust dan E-Service Quality terhadap E-Loyalty (Studi Kasus pada Nasabah Pengguna E-Banking Perbankan Syariah di DKI Jakarta - Firmansyah, Agus; Amrizal, Amrizal (Universitas Batanghari Jambi, 2024)
This research aims to analyze the variables e-trust, e-service quality in influencing the e-loyalty variable either directly or through the mediating role of the e-satisfaction variable. on sharia banking e-banking users. This research developed 20 question items and distributed them via Google form to customers using sharia banking e-banking in DKI Jakarta. A total of 104 data were collected and then analyzed using the Structural Equation Modeling (SEM) analysis tool. The research results show that the variables e-trust, e-service quality have an influence on e-satisfaction. Likewise, e-loyalty can be influenced by e-loyalty and e-satisfaction, while e-service quality fails to influence e-loyalty. In this research, it was also found that the e-satisfaction variable can play its role as an intervening variable between e-trust and e-service quality on e-loyalty.